The Handbook of media audiences - Nightingale, Virginia (Malden Wiley-Blackwell, 2014)
"This handbook offers a comprehensive overview of the complexity and diversity of audience studies in the advent of digital media. -Recognizes and appreciates valuable traditional approaches and identifies how they can be applied to, and evolve with, the changing media world -Offers diverse perspectives from which being an audience, theorizing audiences, researching audiences, and doing audience research are approached today -Argues that the field works best by identifying particular 'audience problems' and applying the best theories and research methods available to solving them -Includes contributions from some of the most outstanding international scholars in the field"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Mass media -- Audiences; Mass media and culture